Ceramic coating diaphragm for lithium battery and preparation method of ceramic coating diaphragm
By using components such as ceramic particles and homemade modified adhesives in the ceramic coated separator and performing plasma surface treatment, the problems of easy peeling of ceramic coated separator at high temperatures, insufficient mechanical strength and complex preparation process are solved, and high safety and low-cost ceramic coated separator are achieved, which improves the cycle life of lithium batteries.
Patent Information
- Application Number
- CN202510393760.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-31
- Publication Date
- 2025-04-29
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing ceramic coated diaphragms are easy to peel off at high temperatures, have insufficient mechanical strength, are complex in preparation process and high in cost, making them difficult to apply on a large scale.
A ceramic coating layer including ceramic particles, homogeneous dispersant, thickener, homemade modified adhesive, wetting agent and diluent is adopted, and plasma surface treatment is carried out to improve the interface compatibility and mechanical strength of the ceramic coating layer and the base film.
It improves the interface compatibility, high mechanical strength and electrochemical properties of ceramic-coated separators, simplifies the preparation process, reduces costs, and enhances the safety and cycle life of lithium batteries.
Smart Images

Figure CN119905779A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium batteries, and in particular to a ceramic coated diaphragm for lithium batteries and a preparation method thereof. Background Art
[0002] As the energy density of lithium batteries continues to increase, their safety issues are becoming increasingly prominent. Traditional polyolefin separators tend to shrink and melt at high temperatures, causing internal short circuits in the battery and thermal runaway. Ceramic coated separators can effectively improve the thermal stability of the separator and enhance battery safety by coating a layer of high-temperature resistant ceramic coating on the surface of the base film.
[0003] However, existing ceramic coated diaphragms still have the following problems:
[0004] 1. The interface compatibility between the ceramic coating and the base film is poor and easy to peel off, affecting the cycle life of the battery.
[0005] 2. The ceramic coating has insufficient mechanical strength and is prone to breakage during battery assembly and use, posing a safety hazard.
[0006] 3. The preparation process of ceramic coating is complicated, the cost is high, and it is difficult to apply on a large scale. Summary of the invention
[0007] The purpose of the present invention is to overcome the deficiencies of the prior art and provide a high-safety ceramic coated diaphragm and a preparation method thereof, wherein the diaphragm has excellent interface compatibility, high mechanical strength and good electrochemical properties, and the preparation process is simple and the cost is low.
[0008] To solve the above technical problems, according to one aspect of the present invention, more specifically, a ceramic coated diaphragm for lithium batteries, the diaphragm comprises a base film and a ceramic coating layer coated on at least one side of the base film, the ceramic coating layer comprising the following components: ceramic particles, a homogenizing dispersant, a thickening agent, a self-made modified adhesive, a wetting agent, and a diluent. The ceramic coating layer is also subjected to a plasma surface treatment.
[0009] Furthermore, the preparation method of the self-made modified adhesive is: add one or more of polyurethane adhesive, polystyrene-butyl acrylate adhesive, and polyvinylidene fluoride adhesive into a reaction bottle, add 3 times the weight of toluene, stir evenly, add 0.11 to 0.16 times the weight of the adhesive complexing agent, heat and reflux for 5 hours. After reflux, evaporate toluene under reduced pressure at 70°C to obtain the self-made modified adhesive.
[0010] Furthermore, the preparation method of the complexing agent is: dissolving a formulated amount of 2-aminomethylpyridine in an N,N-dimethylformamide solvent, dissolving a formulated amount of cupric chloride in an N,N-dimethylformamide solvent, slowly adding the toluene solution of cupric chloride to the toluene solution of 2-aminomethylpyridine, stirring at 30° C. for 3 hours, filtering, beating the filter cake with N,N-dimethylformamide, and filtering to obtain the complexing agent;
[0011] Furthermore, the base film of the present invention is a polyethylene diaphragm or a polypropylene diaphragm, and the thickness of the ceramic coating layer is 4-12 μm;
[0012] Furthermore, the ceramic coating layer of the present invention comprises the following components by weight: 35 to 55 parts of ceramic particles, 4 to 10 parts of homogenizing dispersant, 3 to 8 parts of thickening agent, 15 to 20 parts of homemade modified adhesive, 2 to 6 parts of wetting agent, and 45 to 60 parts of diluent;
[0013] Furthermore, the ceramic particles of the present invention include at least one or more of aluminum nitride, silicon nitride, zirconium oxide, and silicon carbide;
[0014] Furthermore, the homogenous dispersant in the present invention includes at least one or more of cetyl triethyl ammonium bromide, cetyl dimethyl ethyl ammonium bromide, octylphenol polyoxyethylene ether, and acrylic acid polymer;
[0015] Furthermore, the thickening agent of the present invention includes at least one or more of polyvinyl pyrrolidone, sodium carboxymethyl cellulose, and sodium starch phosphate;
[0016] Furthermore, the wetting agent of the present invention includes at least one or more of dodecyl polyoxyethylene ether, nonylphenol polyoxyethylene ether, and dinonylphenol polyoxyethylene ether;
[0017] Furthermore, the diluent of the present invention includes at least one or more of N-methylpyrrolidone, N,N-dimethylformamide, xylene, and ethyl benzene.
[0018] Furthermore, the plasma surface treatment of the present invention includes one of oxygen plasma surface treatment, argon plasma surface treatment and nitrogen plasma surface treatment.
[0019] According to another aspect of the present invention, there is provided a method for preparing a ceramic coated diaphragm for a lithium battery, comprising the following steps:
[0020] S1, adding the formulated amount of ceramic particles and homogenizing dispersant into the diluent, and homogenizing with a homogenizer for 30 minutes, which is recorded as the first mixing system;
[0021] S2, adding the homemade modified adhesive in the formula amount to the first mixed system, and then adding the wetting agent in the formula amount, and homogenizing with a homogenizer for 30 minutes, which is recorded as the second mixed system;
[0022] S3, adding the formulated amount of thickener to the second mixing system, and homogenizing with a homogenizer for 1 hour to obtain a ceramic slurry;
[0023] S4, coating the ceramic slurry on at least one side of the base film, with a layer thickness of 4-12 μm, and drying at a constant temperature of 85° C. for 2 hours to obtain a ceramic coated diaphragm;
[0024] S5. Perform plasma surface treatment on the ceramic coated diaphragm prepared in S4 to obtain a ceramic coated diaphragm for lithium batteries.
[0025] Beneficial Effects
[0026] 1. The present invention makes a modified adhesive by adding a complexing agent. Since the added complexing agent has a certain conductivity, the electronic conductivity of the ceramic coated diaphragm can be improved, the internal resistance of the battery can be reduced, and the ceramic coated diaphragm has good electrochemical properties, which can effectively improve the cycle life of the lithium battery.
[0027] 2. The present invention uses plasma surface treatment technology to effectively improve the interface compatibility between the ceramic coating and the base film, improve the wear resistance and corrosion resistance of the ceramic coated diaphragm, and enhance the overall performance and service life of the ceramic coated diaphragm. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 It is a schematic diagram of the complexing agent structure of the present invention. DETAILED DESCRIPTION
[0029] Embodiment 1
[0030] S1, dissolving 10.8 g of 2-aminomethylpyridine in 21.6 g of N, N-dimethylformamide solvent, dissolving 13.4 g of cupric chloride in 40.2 g of N, N-dimethylformamide solvent, slowly adding the cupric chloride solution to the 2-aminomethylpyridine solution, stirring at 30° C. for 3 h, filtering, beating the filter cake with N, N-dimethylformamide, filtering to obtain a complexing agent;
[0031] S2, add 100g of polyurethane adhesive to a reaction bottle, add 300g of toluene, stir evenly, add 11g of the complexing agent prepared in S1, heat and reflux for 5 hours, after reflux, evaporate toluene under reduced pressure at 70°C to obtain a self-made modified adhesive;
[0032] S3, adding 35 parts of aluminum nitride and silicon nitride mixture and 4 parts of hexadecyltriethylammonium bromide to 45 parts of N,N-dimethylformamide, and homogenizing with a homogenizer for 30 minutes, which is recorded as the first mixed system;
[0033] S4, adding 15 parts of the homemade modified adhesive prepared in step S2 to the first mixed system, and then adding 2 parts of dodecyl polyoxyethylene ether, and homogenizing with a homogenizer for 30 minutes, which is recorded as the second mixed system;
[0034] S5, adding 3 parts of polyvinyl pyrrolidone to the second mixed system, and homogenizing with a homogenizer for 1 hour to obtain a ceramic slurry;
[0035] S6, coating the ceramic slurry on one side of the polyethylene diaphragm with a coating thickness of 12 μm, and drying at a constant temperature of 85° C. for 2 hours to obtain a ceramic coated diaphragm;
[0036] S7. The ceramic coated diaphragm prepared in S6 is subjected to oxygen plasma surface treatment, the power is adjusted to 1 kW, the oxygen pressure is adjusted to 0.3 MPa, and the treatment is performed for 1 minute to obtain a ceramic coated diaphragm for a lithium battery.
[0037] Embodiment 2
[0038] S1, dissolving 10.8 g of 2-aminomethylpyridine in 21.6 g of N, N-dimethylformamide solvent, dissolving 13.4 g of cupric chloride in 40.2 g of N, N-dimethylformamide solvent, slowly adding the cupric chloride solution to the 2-aminomethylpyridine solution, stirring at 30° C. for 3 h, filtering, beating the filter cake with N, N-dimethylformamide, filtering to obtain a complexing agent;
[0039] S2, add a mixture of 50g of polystyrene-butyl acrylate adhesive and 50g of polyvinylidene fluoride adhesive into a reaction bottle, add 300g of toluene, stir evenly, add 11g of the complexing agent prepared in S1, heat and reflux for 5 hours, after reflux, evaporate toluene under reduced pressure at 70°C to obtain a homemade modified adhesive;
[0040] S3, adding 55 parts of silicon nitride and zirconium oxide mixture, 10 parts of hexadecyl dimethyl ethyl ammonium bromide and octylphenol polyoxyethylene ether mixture to 60 parts of xylene and ethyl benzene mixed solvent, and homogenizing with a homogenizer for 30 minutes, which is recorded as the first mixed system;
[0041] S4, adding 20 parts of the homemade modified adhesive prepared in step S2 to the first mixed system, and then adding 6 parts of a mixture of nonylphenol polyoxyethylene ether and dinonylphenol polyoxyethylene ether, and homogenizing with a homogenizer for 30 minutes, which is recorded as the second mixed system;
[0042] S5, adding 8 parts of sodium carboxymethyl cellulose and sodium starch phosphate to the second mixing system, and homogenizing with a homogenizer for 1 hour to obtain a ceramic slurry;
[0043] S6, coating the ceramic slurry on both sides of the polyethylene diaphragm, with a coating thickness of 4 μm on each side, and drying at a constant temperature of 85° C. for 2 hours to obtain a ceramic coated diaphragm;
[0044] S7. Perform nitrogen plasma surface treatment on the ceramic coated diaphragm prepared in S6, adjust the power to 1 kW, adjust the nitrogen pressure to 0.3 MPa, and treat the single side for 1 minute to obtain a ceramic coated diaphragm for lithium batteries.
[0045] Embodiment 3
[0046] S1, dissolving 10.8 g of 2-aminomethylpyridine in 21.6 g of N, N-dimethylformamide solvent, dissolving 13.4 g of cupric chloride in 40.2 g of N, N-dimethylformamide solvent, slowly adding the cupric chloride solution to the 2-aminomethylpyridine solution, stirring at 30° C. for 3 h, filtering, beating the filter cake with N, N-dimethylformamide, filtering to obtain a complexing agent;
[0047] S2, add 100g of polystyrene-butyl acrylate adhesive to a reaction bottle, add 300g of toluene, stir evenly, add 11g of the complexing agent prepared in S1, heat and reflux for 5 hours, after reflux, evaporate toluene under reduced pressure at 70°C to obtain a homemade modified adhesive;
[0048] S3, adding a mixture of 45 parts of silicon carbide, 8 parts of acrylic acid polymer and hexadecyl dimethyl ethyl ammonium bromide to 55 parts of N-methylpyrrolidone, and homogenizing with a homogenizer for 30 minutes, which is recorded as the first mixing system;
[0049] S4, adding 18 parts of the homemade modified adhesive prepared in step S2 to the first mixed system, and then adding 4 parts of nonylphenol polyoxyethylene ether, homogenizing with a homogenizer for 30 minutes, which is recorded as the second mixed system;
[0050] S5, adding 5 parts of sodium carboxymethyl cellulose to the second mixing system, and homogenizing with a homogenizer for 1 hour to obtain a ceramic slurry;
[0051] S6, coating the ceramic slurry on both sides of the polypropylene diaphragm, with a coating thickness of 6 μm on each side, and drying at a constant temperature of 85° C. for 2 hours to obtain a ceramic coated diaphragm;
[0052] S7. The ceramic coated diaphragm prepared in S6 is subjected to argon plasma surface treatment. The power is adjusted to 1 kW, the argon pressure is adjusted to 0.3 MPa, and the single-side treatment is performed for 1 minute to obtain a ceramic coated diaphragm for a lithium battery.
[0053] Comparative Example 1
[0054] S1, adding 35 parts of aluminum nitride and silicon nitride mixture and 4 parts of hexadecyltriethylammonium bromide to 45 parts of N,N-dimethylformamide, and homogenizing with a homogenizer for 30 minutes, which is recorded as the first mixing system;
[0055] S2, adding 15 parts of polyurethane adhesive to the first mixed system, and then adding 2 parts of dodecyl polyoxyethylene ether, and homogenizing with a homogenizer for 30 minutes, which is recorded as the second mixed system;
[0056] S3, adding 3 parts of polyvinyl pyrrolidone to the second mixed system, and homogenizing with a homogenizer for 1 hour to obtain a ceramic slurry;
[0057] S4, coating the ceramic slurry on one side of the polyethylene diaphragm with a coating thickness of 12 μm, and drying at a constant temperature of 85° C. for 2 hours to obtain a ceramic coated diaphragm;
[0058] Comparative Example 2
[0059] S1, adding 55 parts of silicon nitride and zirconium oxide mixture, 10 parts of hexadecyl dimethyl ethyl ammonium bromide and octylphenol polyoxyethylene ether mixture into 60 parts of xylene and ethyl benzene mixed solvent, and homogenizing with a homogenizer for 30 minutes, which is recorded as the first mixed system;
[0060] S2, adding 20 parts of a mixture of polystyrene-butyl acrylate adhesive and polyvinylidene fluoride adhesive to the first mixed system, and then adding 6 parts of a mixture of nonylphenol polyoxyethylene ether and dinonylphenol polyoxyethylene ether, and homogenizing with a homogenizer for 30 minutes, which is recorded as the second mixed system;
[0061] S3, adding 8 parts of sodium carboxymethyl cellulose and sodium starch phosphate to the second mixing system, and homogenizing with a homogenizer for 1 hour to obtain a ceramic slurry;
[0062] S4, coating the ceramic slurry on both sides of the polypropylene diaphragm, with a coating thickness of 4 μm on each side, and drying at a constant temperature of 85° C. for 2 hours to obtain a ceramic coated diaphragm;
[0063] Comparative Example 3
[0064] S1, adding a mixture of 45 parts of silicon carbide, 8 parts of acrylic acid polymer and hexadecyl dimethyl ethyl ammonium bromide to 55 parts of N-methylpyrrolidone, and homogenizing with a homogenizer for 30 minutes, which is recorded as the first mixing system;
[0065] S2, adding 18 parts of the self-made modified adhesive prepared in step S2 to the first mixed system, and then adding 4 parts of nonylphenol polyoxyethylene ether, homogenizing with a homogenizer for 30 minutes, which is recorded as the second mixed system;
[0066] S3, adding 5 parts of sodium carboxymethyl cellulose to the second mixing system, and homogenizing with a homogenizer for 1 hour to obtain a ceramic slurry;
[0067] S4, coating the ceramic slurry on both sides of the polypropylene diaphragm, with a coating thickness of 6 μm on each side, and drying at a constant temperature of 85° C. for 2 hours to obtain a ceramic coated diaphragm;
[0068] Performance Testing
[0069] The performance tests were performed on the ceramic coated diaphragms of Example 1, Example 2, Example 3, Comparative Example 1, Comparative Example 2 and Comparative Example 3. The specific test methods are as follows:
[0070] 1. The bonding strength test of ceramic coating shall be carried out in accordance with the "Test Method for Bonding Strength of Ceramic Coating" (GB / T 39685-2020);
[0071] 2. The porosity test is carried out in accordance with the "Porosity Test Method for Lightweight Porous Materials" (T / CSTM00553-2022);
[0072] 3. The ionic conductivity test is carried out in accordance with the "Test Method for Ionic Conductivity of Power Battery Film" (NB / T10827-2021);
[0073] 4. The wear resistance test is carried out in accordance with the "Falling Sand Method for Determination of Abrasion Resistance of Coatings" (GB / T23988-2009);
[0074] 5. The corrosion resistance test is carried out in accordance with the "Standard Impedance Test Method" (ASTM G106) and the "Lithium Battery Separator Impedance Test" (IEC 62620);
[0075] 6. Battery cycle life test is carried out in accordance with "Requirements and test methods for cycle life of power batteries for electric vehicles" (GB / T31484-2015);
[0076] The test results are shown in the following table:
[0077]
[0078] By comparing the bonding strength of the ceramic coatings of the above three groups of embodiments with the three groups of comparative examples, it can be seen that the bonding strength of the ceramic coatings of the three groups of embodiments is significantly better than that of the three groups of comparative examples, and it can be seen that the plasma surface treatment of the present invention can achieve the effect of enhancing the bonding strength of the ceramic layer; by comparing the porosity of the above three groups of embodiments with the three groups of comparative examples, it can be seen that the porosity of the three groups of embodiments is significantly better than that of the three groups of comparative examples; by comparing the ionic conductivity of the above three groups of embodiments with the three groups of comparative examples, it can be seen that the ionic conductivity of the three groups of embodiments is significantly better than that of the three groups of comparative examples; by comparing the wear resistance data of the above three groups of embodiments with the three groups of comparative examples, it can be seen that the wear resistance of the three groups of embodiments is significantly better than that of the three groups of comparative examples; by comparing the corrosion resistance data of the above three groups of embodiments with the three groups of comparative examples, it can be seen that the corrosion resistance of the three groups of embodiments is significantly better than that of the three groups of comparative examples; by comparing the battery cycle life of the above three groups of embodiments with the three groups of comparative examples, it can be seen that the battery cycle life of the three groups of embodiments is significantly better than that of the three groups of comparative examples; it can be seen that the present invention can make the ceramic coated diaphragm have good electrochemical properties by adding a complexing agent to make a modified adhesive, which can effectively improve the cycle life of the lithium battery.
[0079] Of course, the above description is not a limitation of the present invention. The above description is only a preferred example of the invention. Any changes, modifications, additions or substitutions made according to the content of the present invention are covered by the patent scope of the present invention.
Claims
1. A ceramic coated diaphragm for a lithium battery, characterized in that: The diaphragm comprises a base film and a ceramic coating layer coated on at least one side of the base film, wherein the ceramic coating layer comprises the following components: ceramic particles, a homogenizing dispersant, a thickening agent, a self-made modified adhesive, a wetting agent, and a diluent, wherein the ceramic coating layer is finally subjected to plasma surface treatment; The preparation method of the self-made modified adhesive is as follows: one or more of a polyurethane adhesive, a polystyrene-butyl acrylate adhesive, and a polyvinylidene fluoride adhesive are added to a reaction bottle, 3 times the weight of toluene is added, and after stirring evenly, 0.11 to 0.16 times the weight of the adhesive is added to the complexing agent, and the temperature is raised to reflux for 5 hours. After the reflux is completed, the toluene is evaporated at 70° C. under reduced pressure to obtain the self-made modified adhesive; The preparation method of the complexing agent comprises the following steps: dissolving 2-aminomethylpyridine in N,N-dimethylformamide solvent to obtain a 2-aminomethylpyridine solution, dissolving cupric chloride in N,N-dimethylformamide solvent to obtain a cupric chloride solution, slowly adding the cupric chloride solution into the 2-aminomethylpyridine solution, stirring at 30° C. for reaction for 3 hours, filtering, beating the filter cake with N,N-dimethylformamide, and filtering to obtain the complexing agent.
2. The ceramic coated diaphragm for lithium battery according to claim 1, characterized in that: The base film is a polyethylene diaphragm or a polypropylene diaphragm, and the thickness of the ceramic coating layer is 4-12 μm.
3. The ceramic coated diaphragm for lithium battery according to claim 1, characterized in that: The ceramic coating layer comprises the following components by weight: 35 to 55 parts of ceramic particles, 4 to 10 parts of homogeneous dispersants, 3 to 8 parts of thickeners, 15 to 20 parts of self-made modified adhesives, 2 to 6 parts of wetting agents, and 45 to 60 parts of diluents.
4. The ceramic coated diaphragm for lithium battery according to claim 1, characterized in that: The ceramic particles include at least one or more of aluminum nitride, silicon nitride, zirconium oxide, and silicon carbide.
5. The ceramic coated diaphragm for lithium battery according to claim 1, characterized in that: The homogeneous dispersant includes at least one or more of cetyl triethyl ammonium bromide, cetyl dimethyl ethyl ammonium bromide, octylphenol polyoxyethylene ether, and acrylic acid polymer.
6. The ceramic coated diaphragm for lithium battery according to claim 1, characterized in that: The thickener includes at least one or more of polyvinyl pyrrolidone, sodium carboxymethyl cellulose, and sodium starch phosphate.
7. The ceramic coated diaphragm for lithium battery according to claim 1, characterized in that: The wetting agent includes at least one or more of dodecyl polyoxyethylene ether, nonylphenol polyoxyethylene ether, and dinonylphenol polyoxyethylene ether.
8. The ceramic coated diaphragm for lithium battery according to claim 1, characterized in that: The diluent includes at least one or more of N-methylpyrrolidone, N,N-dimethylformamide, xylene and ethyl benzene.
9. The ceramic coated diaphragm for lithium battery according to claim 1, characterized in that: The plasma surface treatment includes one of oxygen plasma surface treatment, argon plasma surface treatment and nitrogen plasma surface treatment.
10. A method for preparing a ceramic coated diaphragm for a lithium battery according to any one of claims 1 to 9, characterized in that: The following steps are involved: S1, adding the formulated amount of ceramic particles and homogenizing dispersant into the diluent, and homogenizing with a homogenizer for 30 minutes, which is recorded as the first mixing system; S2, adding the homemade modified adhesive in the formula amount to the first mixed system, and then adding the wetting agent in the formula amount, and homogenizing with a homogenizer for 30 minutes, which is recorded as the second mixed system; S3, adding the formulated amount of thickener to the second mixing system, and homogenizing with a homogenizer for 1 hour to obtain a ceramic slurry; S4, coating the ceramic slurry on at least one side of the base film, with a layer thickness of 4-12 μm, and drying at a constant temperature of 85° C. for 2 hours to obtain a ceramic coated diaphragm; S5. Perform plasma surface treatment on the ceramic coated diaphragm prepared in S4 to obtain a ceramic coated diaphragm for lithium batteries.